2013
DOI: 10.1089/tmj.2012.0226
|View full text |Cite
|
Sign up to set email alerts
|

Geomapping Telehealth Access to Developmental-Behavioral Pediatrics

Abstract: Telehealth patients experienced significant reduction in travel times and distances. Patients/families would accept an increased burden of spatial accessibility in exchange for reduced burdens in other aspects of access, such as accommodation or acceptability when engaging telehealth services. Using a road network-based method is more accurate than previously used straight-line methods in calculating distance impedance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…This study, which included 132 patients and 257 telemedicine consultations, found that telemedicine consultative services resulted in an average mileage cost savings of $86.13 [5]. In a third study, the University of Kentucky developmentalbehavioral pediatrics telemedicine program used geographic information systems to determine a median distance and time savings of 63.8 miles and 66.8 minutes, respectively, for each visit as a result of the use of telemedicine [21].…”
Section: Discussionmentioning
confidence: 99%
“…This study, which included 132 patients and 257 telemedicine consultations, found that telemedicine consultative services resulted in an average mileage cost savings of $86.13 [5]. In a third study, the University of Kentucky developmentalbehavioral pediatrics telemedicine program used geographic information systems to determine a median distance and time savings of 63.8 miles and 66.8 minutes, respectively, for each visit as a result of the use of telemedicine [21].…”
Section: Discussionmentioning
confidence: 99%
“…Because ZIP codes do not correspond exactly to county borders, we mapped locations and calculated distances using the centroid methodology that assigns the residence at the geographic center of the ZIP code within a particular county. 19 The centroid approach is a commonly accepted methodology 19, 20 to locate participants in a particular county, in this case allowing comparisons to other studies employing county-based classifications. 12 For all county-level analysis, Missouri counties were categorized as urban or rural based on rural-urban continuum codes that classify counties based on adjacency to a metropolitan statistical area.…”
Section: Methodsmentioning
confidence: 99%
“…Although straight-line distance approximations are known to underestimate actual travel, they never overestimate distance traveled and are commonly used in geographic studies. 20 …”
Section: Methodsmentioning
confidence: 99%
“…A nationwide GIS analysis of VHA SCAN-ECHO across all specialties visualized coverage of mentee sites [6]. A regional U.S. telehealth program was evaluated using GIS and demonstrated substantial travel savings associated with telehealth visits compared with hypothetical inperson visits [8].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, distance from the nearest specialty care provider has been shown to be a barrier in multiple studies. However, prior spatial evaluations of technology-based healthcare programs have been limited to summaries of miles saved and maps of participating clinics [8][9].…”
Section: Introductionmentioning
confidence: 99%